إجراءات التنفيذ القضائي المدني :‏ ‏دراسة مقارنة بين القانون العماني والفقه الإسلامي /‏ - توبي، عبد العزيز بن عبد الله بن حمود
The study aims to examine the civil judicial enforcement in comparison with Islamic jurisprudence, by analyzing the comprehensiveness and effectiveness of legal frameworks and applied procedures of the Omani judiciary in relation to the procedures of judicial enforcement. Moreover, the study examines the extent to which such frameworks are compliant with the principles and rules of the Shariah. The study is based on a central hypothesis that assumes the existence of general rules that regulate the Omani judicial enforcement procedures. However, such rules are not adequate enough to regulate the enforcement procedures and guarantee their effectiveness. The study adopts the historical methodology which is used in tracing the various developments in the codification of judicial enforcement and Islamic Jurisprudence, by going through the most important specific provisions of judicial enforcement. Moreover, the study applies the analytical comparative methodology in analyzing the provisions of judicial enforcement, and comparing the analyzed provisions to find out their similarities and differences. The study consists of a prelude, five chapters, results and conclusion. The first chapter discusses the meaning of enforcement, its importance, purpose, classification, and its legitimacy. The second chapter focuses on the procedures of enforcing civil judicial attachment, which includes attachment of movables owned by the debtor, precautionary attachment, the procedures of enforcing attachment on real estate, the attachment of what is owed to the debtor by other parties and the interdiction of the debtor in Islamic jurisprudence. As for the fourth chapter it deals with the procedures of enforcing civil judicial sales, that includes the procedures for selling movables and the disputes arising out of such sales, preparing the real estate for sale, and the sale of the debtor's property in Islamic jurisprudence. The fifth chapter discusses the distribution of the proceeds of civil judicial enforcement. The study reached a number of results, the most important of which is that the enforcement of judicial injunctions is the main objective behind the establishment of the judiciary, courts, filing of lawsuits, their investigation, their proof, and the issuing of a sentence by the judge. As for the main recommendation of the study it is the need to amend the legislative texts by relying on the injunctions of Islamic jurisprudence so as to facilitate the work of the enforcement directorate and fulfill the requirements of modern times.